The Meaning And Function Of Rerajahan In The Religious Life Of The Balinese Hindu Community - Werdiyasa, I.B. Komang Surya (Bali Tourism Board, 2024)
This abstract provides an overview of rerajahan, a form of sacred symbolism prominent in Bali, often referred to as the Island of the Gods. Rerajahan consists of small cloth pieces adorned with intricate images and inscriptions, such as human figures, mythical creatures, and sacred motifs, displayed on structures like homes and shrines. These symbols, embodying both artistic and spiritual dimensions, serve to invoke blessings and protection, reflecting the deep cultural and spiritual practices of the Balinese community. The term